Factors influencing advanced practitioners' ability to enact leadership: a case study within Irish healthcare. (23rd July 2013) - Higgins, Agnes; Begley, Cecily; Lalor, Joan; Coyne, Imelda; Murphy, Kathy; Elliott, Naomi
<x xml:space="preserve">Abstract</x> Aim To report the factors that influence clinical specialists' and advanced nurse practitioners' ability to enact their clinical and professional leadership roles; findings from the SCAPE study. Background The importance of leadership for specialist and advanced practitioners is highlighted in the international literature and is considered an important factor in the provision of improved patient outcomes. Despite many studies identifying the barriers in developing and integrating new specialist/advanced practice roles into health services, little is known about the factors that influence the leadership dimension of their role. Method A case study design involving 23 clinical specialist/advanced practitioners working in Ireland and multidisciplinary team members working with them, was used. Data were collected using interview, observation and documentary analysis. Results Four mediating factors influence the specialist/advanced practitioner's ability to perform a leadership role, namely the presence of a framework for the professional development of the role; opportunities to act as leaders; mechanisms for sustaining leadership; and personal attributes of practitioners. Conclusion and implications for nursing management Nursing/midwifery leaders and managers at all levels have a key role in supporting leadership potential, through countering the negative impact of professional isolation, expanding opportunities for specialist/advanced practitioners to influence policy and network with wider professional groups.